A novel calibration approach using satellite and visibility observations to estimate fine particulate matter exposures in Southwest Asia and Afghanistan. (2nd January 2017) - Masri, Shahir; Garshick, Eric; Coull, Brent A.; Koutrakis, Petros
ABSTRACT: In order to study effects of ambient particulate matter (PM) it was previously necessary to have access to a comprehensive air monitoring network. However, there are locations in the world where PM levels are above generally accepted exposure standards but lack a monitoring infrastructure. This is true in Iraq and other locations in Southwest Asia and Afghanistan where U.S. and other coalition troops were deployed beginning in 2001. Since aerosol optical depth (AOD), determined by satellite, and visibility are both highly related to atmospheric PM2.5 (particulate matter with an aerodynamic diameter ≤2.5 μm) concentrations, we employed a novel approach that took advantage of historic airport visibility measurements to calibrate the AOD–visibility relationship and determine visibility spatially and temporally (2006–2007) over an approximately 17, 000 km 2 region of Iraq. We obtained daily visibility predictions that were highly associated with satellite-based 1x1 km AOD daily observations ( R 2 =0.87). Based on a previously derived calibration between PM2.5 and visibility, we were able to predict spatially and temporally resolved PM2.5 concentrations. Variability of PM2.5 among sites was high, with daily concentrations differing by as much as ~30 μg/m3. This study demonstrates the feasibility of characterizing historic PM2.5 exposures in Iraq and other locations in Southwest Asia and Afghanistan with similar climate characteristics. This is of utility for epidemiologists seeking to assess the potential health effects related to PM2.5 exposures among previously deployed military personnel and of the population of the region. Implications : This study demonstrates the ability to utilize aerosol optical depth to successfully estimate visibility spatially and temporally in Southwest Asia and Afghanistan. This enables for the estimation of spatially resolved PM2.5 concentrations in the region. The ability to caracterize PM2.5 concentrations in Southwest Asia and Afghanistan is highly important for epidemiologists investigating the relationship between chronic exposure to PM2.5 and respiratory diseases among military personnel deployed to the region. This information will better position policy makers to draft meaningful legislation relating to military health.